INTEGRATION OF TECHNOLOGY IN DA’WAH: UTILIZATION OF SOCIAL MEDIA AND MULTIMEDIA CONTENT TO IMPROVE ACCESSIBILITY AND DA’WAH STRATEGIES OF GUS IQDAM - Risqiatul Hasanah (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2024)
Technology has brought significant changes to various aspects of life, including Islamic dawah. This article explores the integration of technology, especially social media and multimedia content, in efforts to improve accessibility and effectiveness of dawah. With the increasing number of internet and social media users, these platforms offer great opportunities for da’is to reach a wider and more diverse audience. The utilization of social media such as Facebook, Instagram, Twitter, and YouTube enables the delivery of Islamic messages quickly and interactively. Features such as comments, live streaming, and content sharing strengthen the engagement between da’is and the audience, creating a more dynamic and responsive dialogue. In addition, multimedia content such as video lectures, worship tutorials, and documentaries about Islamic history can attract the attention of young audiences, especially Gen Z, who are more familiar with digital formats. This research uses the netnography method with a case study approach. This research also highlights the importance of measuring the effectiveness of dawah through data analytics, which allows for the adjustment of strategies based on audience responses. The included case study demonstrates how Gus Iqdam and the Management of Majelis Ta’lim Sabilu_Taubah successfully integrated technology to expand their reach and increase the impact of their dawah. In conclusion, the integration of technology in dawah is an important step to address the challenges of the modern era and ensure that Islamic messages can be accessed and understood by a wide audience. Da’is are expected to continue to adopt and utilize technology to deliver dawah in a more relevant and effective manner.